Pakistan Tertiary Education : SABER Country Report 2017 - World Bank (World Bank, Washington, DC, 2018)
SABER–Tertiary Education (SABER-TE) is a diagnostic tool to assess how education systems perform and to identify priorities for reforms at the national level. It is part of the World Bank’s Systems Approach for Better Education Results (SABER), which aims to benchmark education systems at the country level. SABER-TE focuses on seven dimensions of tertiary education policy. The general idea is that a strong policy environment is a prerequisite to better-performing tertiary education institutions, including universities, colleges, and technical and vocational institutes. The diagnostic tool aims to help countries assess best practices and to diagnose which policies need urgent attention. For some policy areas, countries are scored on specific ‘policy levers’ to help make concrete recommendations for improvement. Each of the seven policy dimensions can contribute to the outcomes of tertiary education systems, although they work together in a holistic way. By manner of illustration, a strategic plan without an effective governance structure is just a collection of ideas that will not be implemented; a well-designed governance structure without a strategic plan is a meaningless bureaucracy. This report describes the context of the tertiary education system in Pakistan, then proceed with scoring the seven policy dimensions with descriptions, followed by a conclusion with a few general observations and recommendations about tertiary education in Pakistan.